2016
DOI: 10.5530/ijpcs.5.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound Guided Technique with Conventional Landmark Technique for Supraclavicular Brachial Plexus Nerve Block in Patients Undergoing Upper Limb Surgery

Abstract: Background: Brachial plexus blockade is a time tested anesthetic technique for upper limb surgeries. Among the various approaches of brachial plexus block, supraclavicular block, once described as the "spinal of the arm," offers dense anesthesia of the brachial plexus for surgical procedures at or distal to the elbow. Landmark technique has been traditionally used for performing this block. But blind technique often requires multiple trial-and-error needle attempts, resulting in increase in procedure time, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…[9] In our study we have observed higher success rate with supraclavicular approach may be due to the fact that we have used nerve-stimulation technique more than paraesthesia technique. Therefore the complications like pneumothorax found in only one patients which was similar with the study done by Kapral et al [10] & Raghove et al [11] …”
Section: Discussionsupporting
confidence: 78%
“…[9] In our study we have observed higher success rate with supraclavicular approach may be due to the fact that we have used nerve-stimulation technique more than paraesthesia technique. Therefore the complications like pneumothorax found in only one patients which was similar with the study done by Kapral et al [10] & Raghove et al [11] …”
Section: Discussionsupporting
confidence: 78%
“…In our study, time to primary pain-relieving request in cluster US was 269.59±17.01 minutes which was more than 237.33±15.99 notes in the assembly NS. This is statistically important (p<0.0001) [20][21] . William SR et al [11] also conducted comparable learning by means of the same drug amalgamation and the duration is 846 ± 531 min and 652 ± 473 min in the sets US and NS, respectively.…”
Section: Perceptions and Resultsmentioning
confidence: 99%
“…The present study was undertaken to evaluate the success ratio of blocks given with either conventional method or USG guided block. We selected supraclavicular and inter scalene approach of the ease of administration, higher success rate, more reliable and denser blockage of all three trunks 15 . Moreover, there is no sparing of musculocutaneous nerves and axillary nerve and incidence of tourniquet pain is less.…”
Section: Discussionmentioning
confidence: 99%